STATUS KEBERLANJUTAN DIMENSI EKOLOGI BUDIDAYA IKAN PATIN (PANGASIANODON HYPOPHTHALMUS) DALAM PENGEMBANGAN KAWASAN MINAPOLITAN - Yoyo Wiramiharja; Eddy Supriyono; Ernik Yuliana (Jurnal Matematika Sains dan Teknologi, 2018)
Kumpeh Ulu District is a minapolitan area in Muaro Jambi Regency with main commodity of catfish. The purpose of this study was to analyze the sustainability status of ecological dimension of catfish culture in the development of minapolitan area. The study sites were some villages Kumpeh Ulu District: Pudak, Kota Karang, and Lopak Alai. The research design used quantitative approach. Data collection was done through questionnaires, interviews, and field observations. The population of this research is fishers in Kumpeh Ulu District, and the respondents are 48 fishers. Respondents were determined randomly (simple random sampling). Data were analysed using multidimensional scaling (MDS) with the Rap-Patin device has been modified from the RAPFISH program. The result of analysis to nine attributes obtained by index value is 55,40 and the most sensitive attribute is aquaculture waste processing. The sustainability status of the resulting ecological dimension is "sufficiently sustainable". Improvement of index value and sustainability status conducted by increasing the capacity of the aquaculture waste treatment. Kecamatan Kumpeh Ulu merupakan kawasan minapolitan di Kabupaten Muaro Jambi dengan komoditas utama ikan patin. Penelitian ini bertujuan menganalisis status keberlanjutan dimensi ekologi budidaya ikan patin dalam pengembangan kawasan minapolitan. Lokasi penelitian di Desa Pudak, Kota Karang, dan Lopak Alai. Rancangan penelitian menggunakan pendekatan kuantitatif. Pengumpulan data dilakukan melalui kuesioner, wawancara, dan observasi lapangan. Populasi penelitian adalah pembudidaya di Kecamatan Kumpeh Ulu. Responden ditentukan secara acak (simple random sampling), yang berjumlah 48 orang. Analisis data menggunakan multidimensional scaling (MDS) dengan perangkat Rap-Patin, hasil modifikasi dari program RAPFISH. Hasil analisis terhadap sembilan atribut diperoleh nilai indeks sebesar 55,40 dan atribut yang paling sensitif adalah pengolahan limbah budidaya. Status keberlanjutan dimensi ekologi yang dihasilkan adalah â€œcukup berkelanjutanâ€. Perbaikan nilai indeks dan status keberlanjutan dilakukan dengan peningkatan kapasitas pengolahan limbah budidaya.